Philosophical and Methodological Problems of Modern Neurotheology - Aleksey A. Lagunov; Svetlana Yu. Ivanova (RUDN Journal of Philosophy, 2023)
In modern science, research aimed at studying the functioning of the human brain under the influence of various factors of the social and natural environment, including religious practices, both personal and social, is relevant. The purpose of the research is to consider the current state of neurotheology as a new field of knowledge and to analyze the possibilities of its interaction with already existing social and humanitarian disciplines; review, analytical and critical publications of Russian and foreign scientists are used as material for the study. Attention is drawn to the philosophical and methodological problems that neurotheology needs to be resolved in order to determine its place in the modern cognitive space as its organic component. First of all, according to the authors of the article, representatives of this science need to enrich the formed empirical basis with theoretical generalizations, for which it is necessary to implement the principle of interdisciplinarity declared by them and involve specialists from various fields of humanities in the common work. In the hypotheses put forward by neurotheologists, the question of the ontological existence of objects of religious experience is recognized as epistemologically insoluble, however, when constructing a philosophical and worldview concept, it is impossible to limit oneself to such statements; It is noted that the idea developed in neurotheology about the genetic translation of the qualities of the “brain/consciousness” in the process of “cognitive evolution” of mankind returns us to the social deterministic and mechanistic views overcome by modern science. The hope is expressed that neurotheology, having overcome the emerging philosophical and methodological difficulties, will play an important role in the development of Russian science.